Legal Protection for Buyers in Good Faith in Land Sale Agreements Under Hand Without The Presence of The Seller (Case Study of Court Decision Number 81/PDT.G/2024/PN.Son) - Rusilah, Eni; Arifulloh, Achmad; Darmadi, Nanang Sri (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2025)
A buyer in good faith is a buyer who is unaware of any defects or flaws in a sale or purchase. Legal protection for buyers in good faith is based on Article 1338 of the Civil Code concerning agreements that must be executed in good faith and SEMA Number 7 of 2012, which guarantees legal protection for buyers in good faith. This research uses a case approach and a statute approach. Efforts to gain clarity and understanding of the problem based on court decisions and judges' considerations. Secondary data Obtained from library materials, the data is usually arranged in the form of documents including books, documents, research results embodied in reports and so on. Obtained from primary, secondary and tertiary legal materials. The results of the study show that the legal protection of buyers in good faith is based on Court Decision Number 81 / PDT.G / 2024 / PN.Son, namely stating that the buyer (Defendant) is a buyer in good faith and stating that the Defendant's actions are acts of breach of promise (Wanprestasi), this is in accordance with the theory of preventive legal protection which means that the buyer obtains the land rights in good faith based on the sale and purchase agreement. The judge's legal considerations in this case are in line with the theory of legal certainty, namely conducting a local inspection, to find facts in the field, and conducting an examination of evidence and witnesses and conducting an analysis of the sale and purchase agreement. The decision of the District Court at Level 1 has not yet become final, if there is an appeal, the results of this decision can be inversely proportional to the next decision.